PERANCANGAN CORPORATE IDENTITY WAROENG KAKAP LOOMBOK SEBAGAI UPAYA MENCIPTAKAN BRAND AWARENESS - Sari, Ayu Wulan (Jurnal Art Nouveau, 2014)
Abstract : Waroeng Kakap Loombok is a capsicum Surabaya as an attempt to create culinary efforts in the form of a family business. To face stiff competition against competitors penyetan culinary Surabaya. Then in need of a unique corporate identity so that people know to be Waroeng Kakap Loombok. The design purpose of this is to determine how the identity of the company designs Waroeng Kakap Loombok Surabaya brand awareness. the design is done with a qualitative approach, interviews, research, documentation and learning there. These data were analyzed by using data reduction techniques, data presentations, and conclusions. (Pawito, 2007:104). The results of the analysis found that Waroeng Kakap Loombok has a unique characteristic in the flavor and spicy chili sauce variation choice. Surrounding communities still do not know the Waroeng Kakap Loombok. From the process of data analysis, found a design concept or key word